ANALYSIS OF FACTORS IMPLEMENTATION CERDIK BEHAVIOR IN HYPERTENSION PATIENTS OF PRODUCTIVE AGE AT AIR PUTIH HEALTH CENTER - Isnani, Nahara; Nurrachmawati, Annisa; Anggraeni, Ike; Rohmah, Nur; Hardito, Agus; Wati, Ratna (STIKES HUSADA GEMILANG, 2025)
Hypertension is a serious health issue worldwide that can lead to stroke, myocardial infarction, heart failure, dementia, kidney failure, and vision problems, and it poses a significant issue especially for the productive age, as it can reduce work productivity. The CERDIK behavior (Check health regularly, Eliminate cigarette smoke, Regular physical activity/exercise, Healthy and balanced diet, Enough rest, and Manage stress) is one of the ways that can be done to prevent and control hypertension. This study aims to analyze the factors influencing the application of CERDIK behavior among productive age hypertensive patients at Air Putih Community Health Center. This research is an observational study with a cross-sectional approach. The research was conducted from April to June 2024 at the Air Putih Public Health Center in Samarinda City. The sample consisted of 130 people who regularly underwent hypertension checks, selected through simple random sampling. Data was collected using a questionnaire and analyzed using multiple logistic regression testing. The results of the multiple logistic regression analysis indicate that the most significant factors related to CERDIK behavior are self-efficacy (p= 0.000) and self-regulation (p= 0.017). Self-efficacy is a key concept in social cognitive theory. Self-efficacy affects how a person thinks, feels, motivates themselves, and acts. The self-regulation of individuals with hypertension is shaped by beliefs that enhance their ability to implement CERDIK behavior. Hipertensi merupakan masalah kesehatan yang cukup berbahaya diseluruh dunia yang dapat mengakibatkan stroke, infark miokard, gagal jantung, demensia, gagal ginjal, dan gangguan penglihatan dan menjadi permasalahan besar khususnya bagi usia produktif, karena dapat menurunkan produktivitas kerja. Perilaku CERDIK (Cek kesehatan secara berkala, Enyahkan asap rokok, Rajin aktivitas fisik/olahraga, Diet sehat dan seimbang, Istirahat cukup dan Kelola stres) merupakan salah satu cara yang dapat dilakukan untuk mencegah dan mengontrol hipertensi. Penelitian ini bertujuan untuk menganalisis faktor-faktor penerapan perilaku CERDIK pada Penderita Hipertensi Usia Produktif di Puskesmas Air Putih. Penelitian ini adalah penelitian observasional dengan pendekatan cross-sectional. Penelitian dilakukan pada bulan April-Juni 2024 di Puskesmas Air Putih Kota Samarinda. Sampel berjumlah 130 orang yang rutin melakukan pemeriksaan hipertensi yang diambil secara acak sederhana. Pengumpulan data menggunakan kuesioner dan data dianalisis menggunakan uji regresi logistik berganda. Hasil uji analisis regresi logistik berganda menunjukkan faktor yang paling signifikan berhubungan dengan perilaku CERDIK adalah efikasi diri (p= 0,000) dan regulasi diri (p= 0,017). Efikasi diri merupakan gagasan kunci dari teori sosial kognitif (social cognitive theory). Efikasi diri mempengaruhi bagaimana seseorang berpikir, merasa, memotivasi diri sendiri dan bertindak. Regulasi diri penderita hipertensi dibentuk oleh keyakinan yang akan meningkatkan kemampuan untuk menerapkan perilaku CERDIK.